Progress in the treatment of B-cell chronic lymphocytic leukaemia - Lewandowska, Maria; Lewandowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2006)
Chronic lymphocytic B-cell leukaemia (B-CLL) in adults comprised 20-30% of leukemia cases in humans. 90% of the cases is diagnosed in persons over 60 years old and males are two times more frequently affected than women. Recently the adverse prognostic factors were identified, among other things, thymidin kinase activity, β 2 -microglobulin and soluble CD23 receptor content in the plasma. The immunoglobulin gene heavy chain variable region mutational status (VH) and the presence of cytogenetic abnormalities of 17p (p53 gene) and 11q chromosome significantly affect the clinical course of the disease. Deletion or mutation of p53 gene adversely influence overall survival of B-CLL patients and increase 13 times the risk of death in comparison to patients without the defect. Deletion and mutation of the p53 gene are probably responsible for the drug resistance, i.e. purine analogs. For many years alkilating drugs have been used, for example chlorambucil which produced partial response (PR) in a significant number of patients. However, complete response rate (CR) does not exceed 10%. According to recent data alkilating drug tretment does not prolong overall survival (OS). Since the beginning of the eighties, purine analogs (fludarabine, 2-CDA, pentostatin) have been introduced to the treatment of B-CLL. Its administration in a first line treatment produced overall response rates (ORR) in 71-86% of cases. The combination of purine analogs with cyclophosphamide increases response rates. However, in most of the cases minimal residual disease (MRD) is present, even if the CR is obtained. Recently, the monoclonal antibodies (MoAb) reacting with B-lymphocyte epitops were introduced (Rituksimab – CD20, alemtuzumab – CD52) to the treatment of B-CLL patients. In a case of Rituksimab monotherapy OR rates is about 50%, and hematological response is related to the dose of the drug used. Campath-1H monotherapy produced higher response rates up to 80%. However, due to drug related immunosupression the risk of infectious complications occurrence increases, especially CMV. First results of clinical trials confirmed high efficacy of the combination of purine analogs and MoAb. This may significantly increase OS in B-cell CLL patients.